2018
DOI: 10.2174/1570159x15666170705101910
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Reduce Oxidative Stress in Glaucoma Patients

Abstract: Based on the impact of antioxidants and ω-3/ω-6 fatty acids at the molecular level in the glaucomatous anterior and posterior eye segments, further studies are needed by integrating all issues involved in glaucoma pathogenesis, endogenous and exogenous risk factors and their interactions that will allow us to reach newer effective biotherapies for preventing glaucomatous irreversible blindness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 138 publications
0
44
0
2
Order By: Relevance
“…Over the past several decades, oxidative stress has been found to be involved in the pathogenesis and development of many diseases, including ophthalmic diseases (Nishimura et al, 2017;Pinazo-Duran et al, 2018), diabetes (Rochette et al, 2018), cardiovascular diseases (Luscher, 2015;Munzel et al, 2015;Schiattarella and Hill, 2017), atherosclerosis (Forstermann et al, 2017), arthritis (Bala et al, 2017;Kardes and Karagulle, 2018), dermatological diseases (Rojo de la Vega et al, 2018), respiratory diseases (Hecker, 2018), hepatic diseases (Lee et al, 2019), urinary system diseases (Andersson, 2018), cancer (Poprac et al, 2017), neurodegenerative disorders (Jiang et al, 2016), and other nervous system diseases (D'Amico et al, 2013;Patel, 2016;Pei and Fan, 2017). Moreover, oxidative stress also participates in pathological processes after ICH (Aronowski and Zhao, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several decades, oxidative stress has been found to be involved in the pathogenesis and development of many diseases, including ophthalmic diseases (Nishimura et al, 2017;Pinazo-Duran et al, 2018), diabetes (Rochette et al, 2018), cardiovascular diseases (Luscher, 2015;Munzel et al, 2015;Schiattarella and Hill, 2017), atherosclerosis (Forstermann et al, 2017), arthritis (Bala et al, 2017;Kardes and Karagulle, 2018), dermatological diseases (Rojo de la Vega et al, 2018), respiratory diseases (Hecker, 2018), hepatic diseases (Lee et al, 2019), urinary system diseases (Andersson, 2018), cancer (Poprac et al, 2017), neurodegenerative disorders (Jiang et al, 2016), and other nervous system diseases (D'Amico et al, 2013;Patel, 2016;Pei and Fan, 2017). Moreover, oxidative stress also participates in pathological processes after ICH (Aronowski and Zhao, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that oxidative stress is involved in the mechanism of glaucoma development and recent studies suggest the possibility of effects of factors other than IOP [31,32], the effects of lifestyle or nutrient intake may contribute to the development of glaucoma. Calcium plays a role in oxidative stress, and impaired calcium regulation has been implicated in neurodegenerative diseases, including glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…CoQ10 is synthesized endogenously, but it can be taken also as exogenous antioxidant [ 62 , 63 ] and is well tolerated over a wide dosage range, with minimal side effects [ 64 ]. Some authors reported that CoQ10 may have a beneficial effect in the treatment of oxidative phosphorylation disorders [ 65 ] and can reduce oxidative stress in glaucoma patients [ 66 ].…”
Section: Introductionmentioning
confidence: 99%